Analisis Peran Klinik Baca Dalam Meningkatkan Kemampuan Membaca Siswa Kelas II SDN Telang 1 Bangkalan - Zela Salsabila; Andika Adinanda Siswoyo (Journal on Education, 2024)
Education plays an essential role in the development of individuals and nations. One of the main challenges in education is the low reading ability of students, which can hinder the overall learning process. This study aims to analyze the role of the reading clinic in improving the reading skills of second-grade students at SDN Telang 1 Bangkalan. The research employs a descriptive qualitative method, with data collection through observations and interviews with the class teacher. The results show that the implementation of the reading clinic, held every Friday and Saturday, has a significant positive impact. Before the implementation of the reading clinic, only 15 to 17 out of 27 students could read well. After several months of implementation, 51.85% of students were in the excellent category, 44.44% in the good category, 7.4% in the fairly good category, and only 3.7% in the less good category. The reading clinic activities provide intensive and individualized guidance to students struggling with reading, resulting in a significant improvement in their reading abilities. The role of teachers in nine key aspects, as well as the collaboration between teachers and parents, has proven to be very effective in addressing this issue.